Research on Effectiveness and Application of Fixed-Plane Perforation Fracturing Technology in Ultra-Low-Permeability Reservoir - Penghui Duan; Xiaofei Wang; Xiaojia Xue; Xiangping Li; Baoqiang Lv; Xiujie Lei; Jun Bu; Haigang Wang (Geofluids)
Water flooding development of Chang 6 ultra-low-permeability reservoirs in Ansai lasted for more than 30 years; the front of the water drive has swept the reservoir high permeability zone. As a result, a large amount of residual oil stayed in the reservoir longitudinal low-permeability area. To recover the remaining oil in the low-permeability layers, the fixed-plane perforation fracturing technology is proposed, i.e., using fixed-plane perforation to form a sector stress concentration surface perpendicular to the axis of the wellbore, which makes hydraulic fracture expand radially along the wellbore and control the longitudinal direction of the fracture. Based on the study of residual oil distribution and variation of rock mechanics parameters under long-term injection and production conditions, we simulated and analyzed the effect of fracture initiation under different perforation phases. The optimum perforation phase angle was selected according to the size of the fracture fusion area. According to the fracture simulation under the condition of weak stress difference, the parameters of fracturing operation were optimized with controlling fracture height. A 2-fold increase in ultra-low-permeability reservoir production was achieved by fixed-plane perforation fracturing compared with traditional fracturing technology according to the production data of 78 wells. In this paper, we propose a fixed-plane injection fracturing technique to address the problem of tapping the remaining oil in the longitudinal low-permeability section of the reservoir, which can provide support for tapping the remaining oil in the low-permeability section of the extra-low-permeability reservoir.